2019
DOI: 10.1111/modl.12593
|View full text |Cite
|
Sign up to set email alerts
|

Language Education and ‘Conflicted Heritage’: Implications for Teaching and Learning

Abstract: This article revisits discussions of the relationship between language and heritage, bringing into the picture processes and experiences of (in)security and conflict. It draws largely on critical heritage studies literature, as well as on literature that deals with managing heritage in postconflict situations, and uses insights and concepts from this literature to inform current debates in modern language education and heritage language education in particular. Using the notion of conflicted heritage, it focus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Second, the history of conflict and processes of (in)securitization in Cyprus led us to probe the notion of “ heritage language .” Debates on heritage language education have centred on the definition of “heritage speaker” (e.g. Bale, ; Valdés, ), but in Cyprus (and comparable sites mentioned in note 4), “heritage” is highly contested (Charalambous, ), requiring an analysis that is sensitive to the concept’s different economic, cultural, and ideological functions and the power and identity struggles involved. So exactly what, for example, is considered “heritage,” for whom, with what social and political effects?…”
Section: Revising Sociolinguistic Conceptsmentioning
confidence: 99%
“…Second, the history of conflict and processes of (in)securitization in Cyprus led us to probe the notion of “ heritage language .” Debates on heritage language education have centred on the definition of “heritage speaker” (e.g. Bale, ; Valdés, ), but in Cyprus (and comparable sites mentioned in note 4), “heritage” is highly contested (Charalambous, ), requiring an analysis that is sensitive to the concept’s different economic, cultural, and ideological functions and the power and identity struggles involved. So exactly what, for example, is considered “heritage,” for whom, with what social and political effects?…”
Section: Revising Sociolinguistic Conceptsmentioning
confidence: 99%
“…This connects with literature on education in post-authoritarian, post-conflict and divided societies that has regularly underlined the powerful emotional pressures placed on educators in the teaching of sensitive political histories (e.g. Charalambous et al, 2016;Charalambous, 2019;Gregg, 2015;Kello, 2016;Laketa, 2018;Subotic, 2013). In the context of Cyprus, research has shown how 'emotions and memories are "schooled"' in ways that can entrench opposing national discourses, whilst simultaneously impeding teachers' willingness and ability to explore alternative or more reconciliatory approaches to past and present conflicts (Zembylas et al, 2014: 78).…”
Section: Literature Reviewmentioning
confidence: 65%
“…Though many scholarly accounts of HL motivation have traditionally referenced HSs’ desires to connect with their heritage community and culture as a driving force for studying the HL, the reality of this so‐called integrative motivation (Gardner, 2001) is much more complex both theoretically and emotionally (Charalambous, 2019; He, 2008; Huang & Chan, 2024, this issue). Across HLs, speakers did express the goal of making family members proud by learning their HL, but this was often accompanied by hopes of avoiding bringing shame to their family for not speaking the HL (Wang, 2023).…”
Section: Resultsmentioning
confidence: 99%
“…This work suggests that sensations of tension and discomfort in the HL classroom are likely to be accompanied by feelings of anxiety, frustration, and even fear, and that further exploration of emotions in HLE from epistemologies anchored in minoritized histories of displacement and discomfort is warranted. Charalambous (2019) moved beyond traditional education paradigms and theories in FL emotions by drawing on critical heritage studies, which explore how conflict affects the relationship between language and heritage (Smith, 2012), to explore Turkish heritage classes in Greek-Cypriot and the implications of a violent and conflict-ridden history for the Turkish HL classroom. Her evaluation that the relationship between language and heritage is founded in social and political histories of trauma, threat, and dislocation can be applied to HLs around the globe and points to the feelings of (in)security, conflicted identity, and heritage that can arise in any HL classroom.…”
mentioning
confidence: 99%